Observation for assessment of clinician performance: a narrative review. Issue 1 (30th September 2015) - Yanes, Arianna F; McElroy, Lisa M; Abecassis, Zachary A; Holl, Jane; Woods, Donna; Ladner, Daniela P
Abstract : Background: Video recorded and in-person observations are methods of quality assessment and monitoring that have been employed in high risk industries. In the medical field, observations have been used to evaluate the quality and safety of various clinical processes. This review summarises studies utilising video recorded or in-person observations for assessing clinician performance in medicine and surgery. Methods: A search of MEDLINE (PubMed) was conducted using a combination of medical subject headings (MeSH) terms. Articles were included if they described the use of in-person or video recorded observations to assess clinician practices in three categories: (1) teamwork and communication between clinicians; (2) errors and weaknesses in practice; and (3) compliance and adherence to interventions or guidelines. Results: The initial search criteria returned 3215 studies, 223 of which were identified for full text review. A total of 69 studies were included in the final set of literature. Observations were most commonly used in data dense and high risk environments, such as the emergency department or operating room. The most common use was for assessing teamwork and communication factors. Conclusions: Observations are useful for the improvement of healthcare delivery through the identification of clinician lapses and weaknesses that affect quality and safety. Limitations of observations include the Hawthorne effect and the necessity of trained observers to capture and analyse the notes or videos. The comprehensive, subtle and sensitive information observations provided can supplement traditional quality assessment methods and inform targeted interventions to improve patient safety and the quality of care.